Effect of sucrose, inverted sugar and phosphate on cassava starch bio-based films. Mechanical, barrier and thermal properties: Part 1 - Veiga-Santos, P.; Oliveira, L. M.; Sarantopóulos, C. I.G.L. [UNESP]; Cereda, M. P. [UNESP]; Scamparini, A. R.P. (My University, 2011)
Although starch is considered one of the most promising natural polymers forpackaging application, it also presents poor mechanical properties and high moisturesensitivity. To overcome such disadvantages, additives have been successfullyincorporated into starch polymers. The isolated and combined effect of additives(sucrose, inverted sugar and sodium phosphate) on cassava starch biobased filmsprotection performance was evaluated using response surface methodology. The additivesreduced cassava starch films tensile strength and increased elongation percentage. Noeffect was observed on water vapor permeability properties. If lower oxygen permeabilityis requested, samples added with 0.7% sucrose, 1.4% inverted sugar and 0.3% sodiumphosphate presented the best alternative and a good balance between tensile strength (>60kgf/cm2) and elongation percentage (>60%). Two glass transition temperatures wereobserved for all experimental samples, indicating phase separation related to theadditives. Interaction of the film network with phosphate diminished the total mass lossafter an endothermic peak. The exothermic peak was not observed for the control and isprobably a crystallization phenomenon related to the additives. © 2011 by Nova Science Publishers, Inc. All Rights Reserved.
Keywords: Additives; Biofilms; Response surface analysis; Starch